Root coverage procedures for treating single and multiple recession-type defects: an updated cochrane systematic review (2019)
Background:This updated Cochrane systematic review (SR) evaluated the efficacyof different root coverage (RC) procedures in the treatment of single and multiplegingival recessions (GR).Methods:We included randomized controlled trials (RCTs) only of at least 6 months’duration evaluating Miller’s Class I or II GR (≥3 mm) treated by means of RC pro-cedures. Five databases were searched up to January 16, 2018. Random effects meta-analyses were conducted thoroughly.Results:We included 48 RCTs in the SR. The results indicated a greater GR reductionfor subepithelial connective tissue grafts (SCTG)+coronally advanced flap (CAF)compared to guided tissue regeneration with resorbable membranes (GTR rm)+CAF(mean difference [MD]:−0.37 mm). There was insufficient evidence of a differencein GR reduction between acellular dermal matrix grafts (ADMG)+CAF and SCTG+CAF or between enamel matrix derivative (EMD)+CAF and SCTG+CAF. Greatergains in the keratinized tissue width (KTW) were found for SCTG+CAF when com-pared to EMD+CAF (MD:−1.06 mm), and SCTG+CAF when compared to GTRrm+CAF (MD:−1.77 mm). There was insufficient evidence of a difference in KTWgain between ADMG+CAF and SCTG+CAF.Conclusions:SCTG, CAF alone or associated with another biomaterial may be usedfor treating single or multiple GR. There is also some evidence suggesting that ADMGappear as the soft tissue substitute that may provide the most similar outcomes to thoseachieved by SCTG